NAP-2 Secreted by Human NK Cells Can Stimulate Mesenchymal Stem/Stromal Cell Recruitment - Almeida, Catarina R. (Stem Cell Reports, 2016)
Strategies for improved homing of mesenchymal stem cells (MSCs) to a place of injury are being sought and it has been shown that natural killer (NK) cells can stimulate MSC recruitment. Here, we studied the chemokines behind this recruitment. Assays were performed with bone marrow human MSCs and NK cells freshly isolated from healthy donor buffy coats. Supernatants from MSC-NK cell co-cultures can induce MSC recruitment but not to the same extent as when NK cells are present. Antibody arrays and ELISA assays confirmed that NK cells secrete RANTES (CCL5) and revealed that human NK cells secrete NAP-2 (CXCL7), a chemokine that can induce MSC migration. Inhibition with specific antagonists of CXCR2, a receptor that recognizes NAP-2, abolished NK cell-mediated MSC recruitment. This capacity of NK cells to produce chemokines that stimulate MSC recruitment points toward a role for this immune cell population in regulating tissue repair/regeneration.